2015
DOI: 10.1007/s10682-015-9783-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional modularity in a forcible flower mechanism: relationships among morphology, biomechanical features and fitness

Abstract: Flowers may be interpreted as complex combinations of organs functionally coordinated to attract pollinators and to mechanically interact with the pollinator's body, particularly when flower mechanisms are actively handled by pollinators. Thus, a functional modularity of traits in keel flowers (Fabaceae) was expected because of a compartmentalization between attraction and mechanical functions. To test this hypothesis, we used Collaea argentina, a Fabaceae that exhibits typical keel flowers. The force needed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 56 publications
7
8
0
Order By: Relevance
“…This does contrast with the fact that there is a significant phenotypic correlation between the two traits, but as suggested by previous studies, phenotypic correlations are not always good predictors of genetic correlations, even in highly integrated organs as flowers (Gómez et al 2009). Again, this is consistent with the decoupling of petals found in a related species with keel flowers (Córdoba et al 2015). It is thus possible that the phenotypic correlation is caused by shared environmental factors that affect both traits in Ulex flowers, further confirming the importance of studying evolutionary potential in field realistic conditions.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This does contrast with the fact that there is a significant phenotypic correlation between the two traits, but as suggested by previous studies, phenotypic correlations are not always good predictors of genetic correlations, even in highly integrated organs as flowers (Gómez et al 2009). Again, this is consistent with the decoupling of petals found in a related species with keel flowers (Córdoba et al 2015). It is thus possible that the phenotypic correlation is caused by shared environmental factors that affect both traits in Ulex flowers, further confirming the importance of studying evolutionary potential in field realistic conditions.…”
Section: Discussionsupporting
confidence: 83%
“…We found that flower size shows significant heritability, but no detectable heritability in the standard petal area. Comparing petals in papilionoid flowers, Herrera (2001) found that the standard had higher phenotypic variance than other petals across Genisteae, and argued that its role in pollination was smaller than for the keel petals, in a similar way as Córdoba et al (2015). This and our results suggest that this petal might be prone to high environmentally-induced variation, which increases the exposure to stabilising selection, but does not lead to evolutionary change.…”
Section: Discussionsupporting
confidence: 62%
“…For example, the flowers of many members of the legume family (Fabaceae) require pollinators to apply force to access their reward. In some species, such as Spartium junceum, the force required is considerable and exceeds the strength of the honeybee Apis mellifera (Córdoba, Benitez-Vieyra, & Cocucci, 2015;Córdoba & Cocucci, 2011). For accessible rewards, flowers with larger quantities (e.g.…”
mentioning
confidence: 99%
“…Thus, the force of the pollinator is stronger than the force of petals for opening (termed the operative force), with hypotheses existing on how the operative force has adapted to the pollinator (Córdoba & Cocucci ; Córdoba et al . ; Córdoba & Cocucci ). However, the operative force might be related to factors other than the pollinator.…”
Section: Introductionmentioning
confidence: 99%
“…Under these circumstances, only a specific animal with sufficient force to open the petals may pollinate the plant (Brantjes 1981;Claβen-Bockhoff et al 2004;Córdoba & Cocucci 2011). Thus, the force of the pollinator is stronger than the force of petals for opening (termed the operative force), with hypotheses existing on how the operative force has adapted to the pollinator (Córdoba & Cocucci 2011;Córdoba et al 2015;Córdoba & Cocucci 2017). However, the operative force might be related to factors other than the pollinator.…”
Section: Introductionmentioning
confidence: 99%